521PA randomized, phase II study comparing irinotecan versus amrubicin as maintenance therapy after first-line induction therapy for extensive disease small cell lung cancer (HOT1401/NJLCG1401). (24th November 2019) - Baba, K; Tanaka, H; Fujita, Y; Nakamura, A; Kikuchi, E; Kawai, Y; Harada, T; Watanabe, N; Yokouchi, H; Usui, K; Saito, R; Watanabe, H; et al.
Abstract: Background: Cisplatin plus irinotecan (PI) regimen is used for patients with extensive disease (ED)-SCLC. Amrubicin is mainly used for relapsed SCLC. HOT1401/NJLCG1401 trial, open-label randomized phase II trials was designed to assess the benefit of maintenance therapy in patients with ED-SCLC who responded induction therapy. Methods: Eligible patients were aged 20-74 years; had histologically or cytologically confirmed, ED-SCLC. After induction therapy PI (P: 60mg/m2 on day 1, I: 60mg/m2 on days 1, 8, 15, every 4 weeks for 4 cycles), patients who attained CR, PR and SD were randomized to either maintenance irinotecan (I: 60mg/m2 on days 1, 8, every 3 weeks) or amrubicin (A: 35 mg/m2 on days 1-3 every 3 weeks). The primary endpoint is 6-months PFS rate. Results: A total of 34 patients were enrolled from 2014 to 2017. Twenty patients had disease progression or incomplete of induction chemotherapy, finally 14 (41.1%) patients were randomly assigned to receive irinotecan (n = 7) and amrubicin (n = 7). This study was terminated prematurely because of low patient accrual. Of the evaluable patients (n = 34) the overall objective response rate was 73%, median progression free survival was 5.7 months (95% CI: 3.6 -11.8), and median overall survival was 20.1 months (95% CI: 13.7-NR). Six months PFS rate was 47 % (95%CI: 31.4-63.2). Sub group analysis showed the patients receive maintenance group showed longer PFS and OS than those without (15.8 months and 3.5 months, respectively p < 0.001), (15.4 months and NR months, respectively p = 0.0016). There was no difference in median PFS between the patients treated with irinotecan and those with amrubicin (7.4 months and 21.1 months, respectively p = 0.63). The most common adverse events were neutropenia, anemia during maintenance therapy. Grade 3 or higher hematological toxicity was observed more frequently in amrubicin arm. Treatment related death was not observed in this study. Conclusions: Maintenance therapy of irinotecan or amrubicin after induction therapy was well tolerated. Some patients might be effective for maintenance therapy. Clinical trial identification: UMIN 000013882. Legal entity responsible for the study: HOT/NJLCG. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.